Composition at the CuInSe2/ZnO interface: Copper depletion induced by diethyl‐zinc. Issue 9 (13th February 2014) - Hofmann, A.; Janocha, E.; Kelleter, F.; Pettenkofer, C.
<x xml:space="preserve">Abstract</x> The interface formation between epitaxial CuInSe2(112) films and ZnO deposited by metal‐organic MBE is investigated by photoelectron spectroscopy. Reaction of diethyl‐zinc with CuInSe2 leads to the formation of an intrinsic ZnSe layer and copper depletion of the interface. This is associated with Zn doping of the chalcopyrite surface and a Fermi‐level shift toward the conduction band. The implications on the band alignment are discussed.